The protective effects of sesamol and/or the probiotic, Lactobacillus rhamnosus, against aluminum chloride-induced neurotoxicity and hepatotoxicity in rats: Modulation of Wnt/β-catenin/GSK-3β, JAK-2/STAT-3, PPAR-γ, inflammatory, and apoptotic pathways - Karema Abu-Elfotuh; Heba Mohammed Refat M. Selim; Heba Mohammed Refat M. Selim; Omnia Karem M. Riad; Ahmed M. E. Hamdan; Soha Osama Hassanin; Asmaa F. Sharif; Asmaa F. Sharif; Nouran Magdy Moustafa; Nouran Magdy Moustafa; Ayah M.H. Gowifel; Marwa Y. A. Mohamed; et al. (Frontiers in Pharmacology, 2023)
Introduction: Aluminium (Al) is accumulated in the brain causing neurotoxicity and neurodegenerative disease like Alzheimer's disease (AD), multiple sclerosis, autism and epilepsy. Hence, attenuation of Al-induced neurotoxicity has become a “hot topic“ in looking for an intervention that slow down the progression of neurodegenerative diseases.Objective: Our study aims to introduce a new strategy for hampering aluminum chloride (AlCl3)-induced neurotoxicity using a combination of sesamol with the probiotic bacteria; Lactobacillus rhamnosus (L. rhamnosus) and also to test their possible ameliorative effects on AlCl3-induced hepatotoxicity.Methods: Sprague-Dawley male rats were randomly divided into five groups (n = 10/group) which are control, AlCl3, AlCl3 + Sesamol, AlCl3 + L. rhamnosus and AlCl3 + Sesamol + L. rhamnosus. We surveilled the behavioral, biochemical, and histopathological alterations centrally in the brain and peripherally in liver.Results: This work revealed that the combined therapy of sesamol and L. rhamnosus produced marked reduction in brain amyloid-β, p-tau, GSK-3β, inflammatory and apoptotic biomarkers, along with marked elevation in brain free β-catenin and Wnt3a, compared to AlCl3-intoxicated rats. Also, the combined therapy exerted pronounced reduction in hepatic expressions of JAK-2/STAT-3, inflammatory (TNF-α, IL-6, NF-κB), fibrotic (MMP-2, TIMP-1, α-SMA) and apoptotic markers, (caspase-3), together with marked elevation in hepatic PPAR-γ expression, compared to AlCl3 -intoxicated rats. Behavioral and histopathological assessments substantiated the efficiency of this combined regimen in halting the effect of neurotoxicity.Discussion: Probiotics can be used as an add-on therapy with sesamol ameliorate AlCl3 -mediated neurotoxicity and hepatotoxicity.